2015
DOI: 10.1371/journal.pone.0141110
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of Choline Kinase-Alpha Enhances Autophagy in Tamoxifen-Resistant Breast Cancer Cells

Abstract: Choline kinase-α (Chk-α) and autophagy have gained much attention, as they relate to the drug-resistance of breast cancer. Here, we explored the potential connection between Chk-α and autophagy in the mechanisms driving to tamoxifen (TAM) resistance, in estrogen receptor positive (ER+) breast cancer cells (BCCs). Human BCC lines (MCF-7 and TAM-resistant MCF-7 (MCF-7/TAM) cells) were used. Chk-α expression and activity was suppressed by the transduction of shRNA (shChk-α) with lentivirus and treatment with CK37… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 47 publications
1
10
0
Order By: Relevance
“…EBSS and 3-MA co-treatment further decreased cell viabilities in both cell lines, and there was no significant difference between CHO/CTRL and CHO/SP1 (Figure 6B). Although 3-MA inhibits autophagy process in cells, it was previously reported that 3-MA treatment itself induced apoptosis without autophagy [51,52]. The entire blockade of autophagy in cells rather caused apoptosis, even in the absence of starvation.…”
Section: Resultsmentioning
confidence: 99%
“…EBSS and 3-MA co-treatment further decreased cell viabilities in both cell lines, and there was no significant difference between CHO/CTRL and CHO/SP1 (Figure 6B). Although 3-MA inhibits autophagy process in cells, it was previously reported that 3-MA treatment itself induced apoptosis without autophagy [51,52]. The entire blockade of autophagy in cells rather caused apoptosis, even in the absence of starvation.…”
Section: Resultsmentioning
confidence: 99%
“…Although it has anti-estrogen activity, TAM is widely used to treat ER-positive breast tumors as an adjuvant therapy for early-stage hormone-sensitive breast cancer or first line therapy for metastatic hormone-sensitive breast cancer, and as many as 30% of patients can be refractory to TAM and acquire resistance to TAM along with the loss of ER-α [ 6 , 22 24 ]. CK-α is one of the targets of therapeutic strategies because it is a key enzyme in choline metabolism and might contribute to TAM resistance [ 11 , 19 ]. In addition, the metabolic survival-promotion function of autophagy, which is activated in drug resistant BCCs, is also one of the therapeutic targets [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…CK-α is one of the targets of therapeutic strategies because it is a key enzyme in choline metabolism and might contribute to TAM resistance [ 11 , 19 ]. In addition, the metabolic survival-promotion function of autophagy, which is activated in drug resistant BCCs, is also one of the therapeutic targets [ 19 ]. Our recent study reported a potential connection between autophagy and CK-α in the mechanisms driving TAM resistance in ER+ BCCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overexpression of the CHKα protein can transform noncancerous cells into cells with a cancerous phenotype, and conversely, knockdown of the CHKα protein by siRNA can result in cancer cell death [14]. It has also been shown that siRNA mediated knockdown of CHKA results in upregulation of autophagy, which was further associated with a reduction in cell proliferation in breast cancer cell lines [15]. The precise molecular mechanism underlying this link between choline metabolism and autophagy is unclear.…”
Section: The Role Of Chkαmentioning
confidence: 99%